Immunology of the Uterine and Vaginal Mucosae. Issue 4 (April 2018) - Zhou, Jordan Z.; Way, Sing Sing; Chen, Kang
Abstract : Along with the maintenance of symbiotic mutualism with commensal microbes and protection against invasive infections common to all mucosal barrier tissues, female reproductive tissues have additional, unique tasks that include dynamic cyclic cellular turnover in menstruation and immunological tolerance to genetically foreign fetal antigens in pregnancy. Here we review current knowledge on distinct features of the immune cells in female reproductive tissue with regard to antimicrobial host defense and adaptations to accommodate the fetus during pregnancy. Outstanding areas for future research to obtain new functional insights on this enigmatic mucosal barrier are also highlighted. Highlights: The vaginal mucosa is populated by several APC populations with distinct inflammatory or tolerogenic properties. Resident memory T cells in the vaginal mucosa mediate rapid protection on infection of this tissue. CD4 + T cell entry into the tissue facilitates the entry of circulating memory CD8 + T cells through the production of IFN-γ. Uterine immune cells are functionally adapted to the changing environment during the menstrual cycle. For example, endometrial/decidual NK cells and macrophages have mixed inflammatory, regulatory, and pro-remodeling functions that are optimized for menstruation, placentation, and fetal tolerance. The vaginal immune systems must coordinate with the local microbiota to maintain mucosal homeostasis. There is controversy surrounding the existence of a microbiota in the human placenta. Some studies found traces of microbial products in the womb but other studies refute these claims in favor of a sterile womb hypothesis.